2002
DOI: 10.1038/sj.ejcn.1601370
|View full text |Cite
|
Sign up to set email alerts
|

Diet and 20-year chronic obstructive pulmonary disease mortality in middle-aged men from three European countries

Abstract: Objective: To investigate the relation of baseline antioxidant, fruit, vegetable and fish intake with 20 y chronic obstructive pulmonary disease (COPD) mortality in middle-aged men from three European countries. Design: Prospective study (1970 -1990). Setting: Five population-based cohorts of middle-aged men from Finland, Italy and The Netherlands. Subjects: A total of 2917 men aged 50 -69 y at baseline. Methods: Baseline information on diet was collected using the cross-check dietary history method. After 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
80
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 25 publications
12
80
1
Order By: Relevance
“…Previously, an inverse association between consumption of fruits, but not vegetables, and COPD mortality was observed [36]. Conversely, a diet characterized by high consumption of fruits, vegetables, whole grains, polyunsaturated fatty acids, nuts, and long-chain omega-3 fats and low consumption of red and processed meat, refined grains, and sugar-sweetened drinks was associated with a lower risk of COPD in men and women in the United States [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, an inverse association between consumption of fruits, but not vegetables, and COPD mortality was observed [36]. Conversely, a diet characterized by high consumption of fruits, vegetables, whole grains, polyunsaturated fatty acids, nuts, and long-chain omega-3 fats and low consumption of red and processed meat, refined grains, and sugar-sweetened drinks was associated with a lower risk of COPD in men and women in the United States [37].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, seventeen further articles were sourced in which validation and/or reliability testing for the identified methods was described. The characteristics of the included studies (4,18, are described in Table 2. From the sourced articles, fifty-one pan-European studies in total were identified: thirty-five named projects and sixteen smaller projects (48,54,56,65,69,72,82,83,88,93,94,107,109,113,114,116) .…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…Five assessed parents or caregivers (27,50,(85)(86)(87)102) . Four studies examined intake among older adults, namely MEDIS (MEDiterranean Islands Study) (78) , the Seven Countries Study (4,91,92) , SENECA (Survey in Europe on Nutrition and the Elderly; a Concerted Action) (43,90,148,149) and the 'Food in later life' study (68) . Nine studies assessed intake among children (27,30,37,50,85,86,101,116,120) in age ranges 2-9 years (37,118,119) , 3-6 years (95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106) , 2-11 years (50) , 7-11 years (116) , 11 years (85) and 10-12 years (27) , and seven assessed intake among adolescents (32,50,109,110,…”
Section: Public Health Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, rodent or human trials evaluating this possibility appear to be lacking, as does epidemiology focusing specifically on phase IIinducer foods. Nonetheless, a number of epidemiological studies have concluded that lung function is superior, and risk for COPD lower, in people who consume relatively large amounts of fruits and / or vegetables [5][6][7][8][79][80][81][82]. Hence, it is prudent to advise smokers to consume fruits and vegetables regularly and copiously, with emphasis on cruciferous and allium vegetables.…”
Section: Adjuvant Strategies Targeting Nrf2mentioning
confidence: 99%